ESG actions, corporate discourse, and market assessment nexus: evidence from the oil and gas sector - Horobet, Alexandra; Bulai, Vlad; Radulescu, Magdalena; Belascu, Lucian; Dumitrescu, Dan Gabriel (Journal of Business Economics and Management, 2024)
This paper focuses on the oil and gas sector because of its direct exposure to the complete range of ESG challenges, as well as strong pressure to change business models due to the energy transition. We investigate the ESG scores of a sample of global companies in this sector and their relationship to stock market performance and to the ESG intensity of corporate reports. As an original contribution, we incorporate the intensity of corporate discourse on technology-related sustainability topics for the first time in the literature. Our findings reveal that investors examine both sustainability discourse and results when determining a company’s value and validate the role of ESG scores and rankings in providing investors with an accurate and meaningful assessment of companies’ sustainability actions. Moreover, companies’ disclosure of their sustainable actions and technological developments related to sustainability is positively related to stock returns. This implies that a focus on sustainable practices and constant communication with investors might result in higher market performance. Furthermore, encouraging companies, particularly those in sectors and industries sensitive to ESG factors, to invest in ESG initiatives, is accompanied by improved performance, which makes them more attractive and better positioned to attract financing.